Does sexual Intimate Partner Violence (IPV) increase risk of multiple high-risk fertility behaviours in India: evidence from National Family Health Survey 2015-16 - Milan Das; Csaba G. Tóth; Neha Shri; Mayank Singh; Babul Hossain (BMC, 2022)
Abstract Background One in three women from lower and middle-income countries are subjected to physical and/or sexual intimate partner violence (IPV) in their life span. Prior studies have highlighted a range of adverse health impacts of sexual IPV. However, less is known about the link between multiple high-risk fertility behaviours and sexual intimate partner violence. The present study examines the statistical association between multiple high-risk fertility behaviours and sexual intimate partner violence among women in India. Methods The present study used a nationally representative dataset, the National Family Health Survey (NFHS-4) 2015-16. A total of 23,597 women were included in the study; a subsample of married women of reproductive age who have had at least one child 5 years prior to the survey and who had valid information about sexual IPV. Logistic regression models were employed alongside descriptive statistics. Results Approximately 7% of women who are or had been married face sexual IPV. The prevalence of sexual violence was higher among women who had short birth intervals and women who had given birth more than three times (12%). Around 11% of women who had experienced any high-risk fertility behaviours also experienced sexual violence. The unadjusted association suggested that multiple high-risk fertility behaviours were 32% (UORs = 1.32, 95% CI: 1.16-1.50) higher for those women who experienced sexual violence. After adjusting for other sociodemographic variables, except for women's education and wealth quantile, the odds of multiple high-risk fertility behaviours were 16% (AOR = 1.16; 95% CI: 1.02-1.34) higher among women who faced sexual violence. The inclusion of women's educational attainment and wealth status in the model made the association between sexual IPV and high-risk fertility behaviours insignificant. Conclusion Sexual intimate partner violence is statistically associated with high-risk fertility behaviours among women in India. Programs and strategies designed to improve women's reproductive health should investigate the different dimensions of sexual IPV in India.